Long-term environmental exposure of darkness induces hyperandrogenism in PCOS via melatonin receptor 1A and aromatase reduction - Chu, Weiwei; Li, Shang; Geng, Xueying; Wang, Dongshuang; Zhai, Junyu; Lu, Gang; Chan, Wai-Yee; Chen, Zi-Jiang; Du, Yanzhi (Frontiers in Cell and Developmental Biology, 2022)
Polycystic ovary syndrome (PCOS) is a common and complex disorder impairing female fertility, yet its etiology remains elusive. It is reported that circadian rhythm disruption might play a crucial role in PCOS pathologic progress. Here in this research, we investigated the effect of environmental long-term circadian rhythm dysfunction and clarified its pathogenic mechanism in development of PCOS, which might provide the targeted clinical strategies to patients with PCOS. Female SD rats were used to construct circadian rhythm misalignment model with constant darkness (12/12-h dark/dark cycle), and the Control group was kept under a normal circadian rhythm exposure (12/12-h light / dark cycle) for 8 weeks. We measured their reproductive, endocrinal, and metabolic profiles at different zeitgeber times (ZT). Different rescue methods including melatonin receptor agonist and normal circadian rhythm restoration, and in vitro experiments in KGN cell line were performed. We found long-term darkness caused PCOS-like reproductive abnormalities, including estrous cycle disorder, polycystic ovaries, LH elevation, hyperandrogenism, and glucose intolerance. Besides, the expression of melatonin receptor 1a (Mtnr1a) in ovarian granulosa cells significantly decreased in Darkness group. Normal light / dark cycle and melatonin receptor agonist application relieved hyperandrogenism of darkness-treated rats. In vitro experiments demonstrated decreased MTNR1A inhibited androgen receptor (AR) and CYP19A1 expression, and AR acted as an essential downstream factor of MTNR1A in modulating aromatase abundance. Overall, our finding demonstrates significant influence of circadian rhythm in PCOS occurrence, suggests MTNR1A and AR play vital parts in pathological progress of hyperandrogenism, and broadens current treatment strategies for PCOS in clinical practice.